FINTECH 4.0 TRAINING TO INCREASE CAPITAL AND BUSINESS INCOME FOR SME IN ULAK BANDING VILLAGE, INDRALAYA - Hidayat, Ariodillah; Liliana, Liliana; Bashir, Abdul; Yunisvita, Yunisvita; Andaiyani, Sri; Adnan, Nazeli (LPPM Univ. Ibn Khaldun Bogor, 2023)
During the COVID-19 pandemic, SME in Indonesia became one type of business that was able to adapt and survive and even become a solution for improving the national economy. Fintech has supported SME to develop their business through collaboration with e-commerce partners. This is very helpful for SME during the Covid-19 pandemic. In increasing the capacity of SME actors towards fintech, it is necessary to provide permanent assistance such as digital training. It is intended that actors have digital skills which are expected to have an impact on their financial capabilities. Ulak Banding Village is one of the villages in South Sumatra, Ogan Ilir Regency where SME in the village still lack information about fintech. The problem of SME in Ulak Banding Village in terms of financing can be overcome with capital assistance from peer to peer (P2P) lending and crowdfunding. As well as to increase revenue using digital payment transfers through digital wallet applications, marketplaces, and social media. The training participants are expected to play an active role in increasing capital and expanding their business and transmitting the knowledge they have acquired to other SME.